PRIORITIES IN INSTITUTIONAL TRANSFORMATION OF ECONOMY OF MODERN UKRAINE - Нікіфоров, Петро Опанасович; Бабух, Ілона; Поченчук, Галина (Publishing House Helvetica, 2020)
The existing economic model in Ukraine by its basic properties does not require innovation, it does not involve investment in human capital. In today's context, the restructuring of the economic model of Ukraine is urgently needed, which should be refocused on stimulating and financially supporting large financial and industrial capital for the development of competition, optimizing the regulatory functions of the state and its role in the national reproduction process, significant activation of small and medium-sized businesses. In terms of institutional transformation, the strategic task of the current stage of reforming the national economy is to build an effective system of governance at all levels, to identify new roles at different levels of government, which implies the optimal combination of decentralization and the coordinating, stimulating role of the center.
ПРІОРИТЕТИ В ІНСТИТУЦІОНАЛЬНИХ ТРАНСФОРМАЦІЯХ ЕКОНОМІКИ СУЧАСНОЇ УКРАЇНИ
Keywords: institutional transformation; institutional reform; model of economy; legal state; civil society; governing system; institutional management